Challenging Neoliberalism in Latin America - Silva, Eduardo (Cambridge University Press, 2009)
At the turn of the twentieth century, a concatenation of diverse social movements arose unexpectedly in Latin America, culminating in massive anti-free market demonstrations. These events ushered in governments in Argentina, Bolivia, Ecuador, and Venezuela that advocated socialization and planning, challenging the consensus over neoliberal hegemony and the weakness of movements to oppose it. Eduardo Silva offers the first comprehensive comparative account of these extraordinary events, arguing that the shift was influenced by favorable political associational space, a reformist orientation to demands, economic crisis, and mechanisms that facilitated horizontal linkages among a wide variety of social movement organizations. His analysis applies Karl Polanyi's theory of the double movement of market society to these events, predicting the dawning of an era more supportive of government intervention in the economy and society.
Political Science
Keywords: Latin America; double movement; market society; neoliberalism; political science / comparative politics; political science / world / general

The Extended Case Method: Four Countries, Four Decades, Four Great Transformations, and One Theoretical Tradition - Burawoy, Michael (University of California Press, 2009)
In this remarkable collection of essays, Michael Burawoy develops the extended case method by connecting his own experiences among workers of the world to the great transformations of the twentieth century—the rise and fall of the Soviet Union and its satellites, the reconstruction of U.S. capitalism, and the African transition to post-colonialism in Zambia. Burawoy's odyssey began in 1968 in the Zambian copper mines and proceeded to Chicago's South Side, where he worked as a machine operator and enjoyed a unique perspective on the stability of advanced capitalism. In the 1980s, this perspective was deepened by contrast with his work in diverse Hungarian factories. Surprised by the collapse of socialism in Hungary in 1989, he journeyed in 1991 to the Soviet Union, which by the end of the year had unexpectedly dissolved. He then spent the next decade studying how the working class survived the catastrophic collapse of the Soviet economy. These essays, presented with a perspective that has benefited from time and rich experience, offer ethnographers a theory and a method for developing novel understandings of epochal change.
Sociology
Keywords: social science; sociology

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Anthropology; History
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Karl Polanyi's Great Transformation and Development Politics - Deutschmann, Moritz (Grin Verlag, 2009)
English, abstract: Attempts to understand the transformation processes in the developing world have often led to a closer examination of Europe′s and America′s own history, as many theories of development suggest a specific interpretation of these histories: Modernization theorists, for example, see Europe′s and America′s history mainly as a straightforward progression towards welfare and democracy, eclipsing the aspects that do not fit into this picture, like the World Wars or the American Civil War. Therefore, although Karl Polanyi′s "The Great Transformation" treats mainly historical events in Europe, it can at the same time be an important contribution to our understanding of the economic and social transformations in the developing world. In this essay, I will first try to make clear, what assumptions underlie Polanyi′s argument and what he means by the notion of "market society." I will proceed in three steps: first, I will explore the different roles that the economy, according to Polanyi, plays in capitalist and pre-capitalist societies; I will look then at the historical processes that led to the rise of a "market society." Finally, I will discuss the political reactions to these processes which can be characterized, in Polanyi′s view, by a "double movement." As Polanyi is one of the most important critics of economic liberalism, it is helpful to compare his account of the "Great Transformation" to a second, even more influential anti-liberal perspective, Marxism. Apart from some similarities, the fundamental difference seems to be that Polanyi does not give a positive account of modernization. This leads to the question, how Polanyi′s theori
Political Science
Keywords: Great Transformation; The (Book); development; double movement; market society; modernization